Artistic Experimentation in Music: An Anthology - Crispin, Darla; Gilmore, Bob 1961-2015 (Leuven Leuven University Press, 2014)
Essential reading for anyone interested in artistic research applied to music This book is the first anthology of writings about the emerging subject of artistic experimentation in music. This subject, as part of the cross-disciplinary field of artistic research, cuts across boundaries of the conventional categories of performance practice, music analysis, aesthetics, and music pedagogy. The texts, most of them specially written for this volume, have a common genesis in the explorations of the Orpheus Research Centre in Music (ORCiM) in Ghent, Belgium. The book critically examines experimentation in music of different historical eras. It is essential reading for performers, composers, teachers, and others wanting to inform themselves of the issues and the current debates in the new field of artistic research as applied to music. The publication is accompanied by a CD of music discussed in the text, and by an online resource of video illustrations of specific issues.ContributorsPaulo de Assis (ORCiM), Richard Barrett (Institute of Sonology, The Hague), Tom Beghin (McGill University), William Brooks (University of York, ORCiM), Nicholas G. Brown (University of East Anglia), Marcel Cobussen (University of Leiden), Kathleen Coessens (Vrije Universiteit Brussel, ORCiM); Paul Craenen (Director Musica, Impulse Centre for Music), Darla Crispin (Norwegian Academy of Music), Stephen Emmerson (Queensland Conservatorium, Griffith University, Brisbane), Henrik Frisk (Malmö Academy of Music), Bob Gilmore (ORCiM), Valentin Gloor (ORCiM), Yolande Harris (Center for Digital Arts and Experimental Media DXARTS), University of Washington, Seattle), Mieko Kanno (Royal Conservatoire of Scotland), Andrew Lawrence-King (Guildhall School of Music and Drama, London, Royal Danish Academy of Music, Copenhagen, University of Western Australia), Catherine Laws (University of York, ORCiM), Stefan Östersjö (ORCiM), Juan Parra (ORCiM), Larry Polansky (University of California, Santa Cruz), Stephen Preston, Godfried-Willem Raes (Logos Foundation, Ghent), Hans Roels (ORCiM), Michael Schwab (ORCiM, Royal College of Art, London, Zurich University of the Arts), Anna Scott (ORCiM), Steve Tromans (Middlesex University), Luk Vaes (ORCiM), Bart Vanhecke (KU Leuven, ORCiM)